Libya Archaeological Guides - Kenrick, Philip (Society for Libyan Studies, 2009)
This is a new series of guides to the archaeology of Libya, from prehistoric times until the invasion of the Bani Hilal in AD 1051, written by acknowledged experts for the non-specialist traveler. The first volume, TRIPOLITANIA by Philip Kenrick, deals with a region which offers the visitor not only the classical splendors of UNESCO World Heritage Sites such as Sabratha and Lepcis Magna, but also a hinterland which is rich in standing monuments of the Punic, Roman and early Islamic periods. All are described and explained in a comprehensive gazetteer.